Comparative study of clinical profile of lean and obese polycystic ovary syndrome women - S., Akshaya; Bhattacharya, Ratnaboli (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder of reproductive-aged women, with an estimated prevalence of 4-8% and is the most frequent cause of oligoanovulatory infertility. The objective was to compare the clinical profile of PCOS in lean PCOS (body mass index (BMI) <23 kg/m2) and obese PCOS (BMI >23 kg/m2) women. Methods: Fifty healthy women who were euthyroid with age range 15-38 years who presented to gynecology OPD and diagnosed to have PCOS according to ESHRE/ASRM criteria were included in the study. BMI (body mass index) was calculated by the formula weight in kg/ height in meter square. BMI were calculated were divided into 2 groups. Lean PCOS found in patients with BMI<23 kg/m2 and overweight/obese PCOS found in patients with BMI >23 kg/m2. History of menstrual irregularity, hirsutism, acne, alopecia, infertility, history of weight gain, history of voice change, family history of PCOS, diabetes were taken. Waist to hip ratio and Ferriman- Gallway score were measured in all patients. Results: There was no statistically significant difference in the menstrual irregularities, features of hyper androgenism (hirsutism, infertility, acne, alopecia, clitoromegaly) in both lean and obese PCOS. FG score was more in obese PCOS than in lean PCOS. Weight gain, obesity of abdominal type with higher waist to hip ratio (>0.85) were present in all obese as it was the main criteria for group B. Conclusions: More than half of women with PCOS were obese. The clinical features like menstrual disturbances, infertility, hirsutism, acne and acanthosis nigricans were present in most of PCOS women irrespective of weight. It is noteworthy that even modest weight loss through diet interventions and increased physical activity has favourable effects on reproductive outcome in PCOS.